Milk exosomes-mediated miR-31-5p delivery accelerates diabetic wound healing through promoting angiogenesis. (31st December 2022) - Yan, Chengqi; Chen, Jing; Wang, Cheng; Yuan, Meng; Kang, Yu; Wu, Zihan; Li, Wenqing; Zhang, Guolei; Machens, Hans-Günther; Rinkevich, Yuval; Chen, Zhenbing; Yang, Xiaofan; et al.
Abstract: The refractory diabetic wound has remained a worldwide challenge as one of the major health problems. The impaired angiogenesis phase during diabetic wound healing partly contributes to the pathological process. MicroRNA (miRNA) is an essential regulator of gene expression in crucial biological processes and is a promising nucleic acid drug in therapeutic fields of the diabetic wound. However, miRNA therapies have limitations due to lacking an effective delivery system. In the present study, we found a significant reduction of miR-31-5p expression in the full-thickness wounds of diabetic mice compared to normal mice. Further, miR-31-5p has been proven to promote the proliferation, migration, and angiogenesis of endothelial cells. Thus, we conceived the idea of exogenously supplementing miR-31-5p mimics to treat the diabetic wound. We used milk-derived exosomes as a novel system for miR-31-5p delivery and successfully encapsulated miR-31-5p mimics into milk exosomes through electroporation. Then, we proved that the miR-31-5p loaded in exosomes achieved higher cell uptake and was able to resist degradation. Moreover, our miRNA-exosomal formulation demonstrated dramatically improved endothelial cell functions in vitro, together with the promotion of angiogenesis and enhanced diabetic wound healing in vivo . Collectively, our data showed the feasibility of milk exosomes as a scalable, biocompatible, and cost-effective delivery system to enhance the bioavailability and efficacy of miRNAs.